A música como recurso terapêutico na intervenção junto ao idoso com demência institucionalizado - MORAIS, Anne Carolina de Carvalho (2023)
Objectives: The present study aims to verify the benefits of the use of music in mitigating the negative effects of the institutionalization process, and to evaluate which cognitive aspects change by using music as an occupational therapeutic resource. Methods: This is a quantitative and qualitative exploratory research, such as an uncontrolled clinical trial conducted in a long-term care facility. Participated in interventions, elderly in dementia process residing in the institution. As research, tools it was used the Mini Mental State Exam. Results: The study included three institutionalized elderly, 2 women and 1 man, with an average age of 82.3 years (SD = 8.2, range = 7292), with 0 to 3 years of schooling according to the Mini. Mental State Examination (MMSE) and all participants mentioned enjoying listening to music. All three participants scored below the MMSE cutoff point, indicating cognitive impairment. This test was applied twice, the first during the initial assessment, and the second after intervention with music. The elderly maintained or performed better in MMSE items after the music intervention. Conclusion: This study suggests that music may have positive effects on some cognitive aspects of institutionalized elderly with dementia, especially regarding temporal, spatial orientation, short-term memory, and language. In addition, participants were more communicative and interactive.